Covid-19, teleworking and administration of justice: or how other viruses make our rule of law sick (Acta Judicial Journal, 2020)
In recent years we have spent time reflecting on the protection of personal data and its compliance, application and influence in the Judiciary. Now, after the declaration of a State of Alarma and in astonished expectation for the events that have occurred, and especially, for the decisions that have been adopted, we undertake this work so that it may serve, perhaps, as a lugrubious testimony of the garantee of a fundamental right condemned, in the judicial sphere, to be a mere nominality because there is probably no longer personal data to protect.
Keywords: Data protection, fundamental right, legal security, teleworking, privacy, separation of powers